Mean amplitudes of vibration of the trans-IO2F4¯anion - Barán, Enrique José (2004)
The mean amplitudes of vibration of the trans-IO2F4¯ anion have been calculated from known spectroscopic data between 0 and 1000 K. Bond peculiarities are discussed in comparison with those of trans-IO2F52- and of some other structurally related species.